The silent patient - Michaelides, Alex 1977- (New York [United States] Celadon Books, 2019)
Criminal psychotherapist Theo Faber becomes dangerously obsessed with uncovering the truth about what prompted his client, an artist who refuses to speak, to violently murder her husband in a way that triggers mass public speculation
Keywords: Artists -- Fiction; Family violence -- Fiction; Marriage -- Fiction